Perencanaan Bisnis Fashion Hijab - Anita Anita (Universitas Tarumanagara, 2019)
”Perencanaan Bisnis Fashion Hijab” is a business plan in the field of creative industries. With many of Muslim communities, it is an opportunity for startup to plan the business, especially in the Hijab fashion industry. This business plan aims to create a new business plan for the creative industry engaged in fahion hijab and creating investment opportunities for investors. Based on the results of the analysis and discussion, it can be concluded that this business is feasible to be realized on the basis of consideration, among others, because the market potential of the hijab fashion business is increasing. Financial planning that shows this business will provide profit for investors and is worthy of being realized. Analysis of financial instruments consisting of a payback period which shows the number 4 equal to the maximum time set, the Net Present Value value with a value of Rp. 522,051,842, - or greater than zero indicates this investment can produce an income level that exceeds the requested level and an Internal Rate of Return value of 35% higher than the deposit interest rate.